B4C‐Reinforced Al–Zn Foams Having Superior Energy Absorption Efficiency. Issue 1 (11th September 2022) - Sharma, Ankit; Kanyadhan Vijayaraghavan, Sai Srinivasan; Gupta, Amit Kumar; Ravindran, Sujith
Abstract : The low density of the aluminium foam and high energy absorption make them favourable for automobile, aerospace, and defence industries. However, the melt route for foam fabrication has challenges in achieving homogeneous distribution of pores. Hence, we have adopted the space holder technique using the powder metallurgy methodology to overcome such a challenge. In the current study, we fabricated Al–Zn alloy foams reinforced with varying volume fractions of B4 C particles using NaCl as a space holder implemented by hot pressure‐assisted sintering and dissolution. X‐ray computed tomography revealed a homogeneous distribution of pores. The quasistatic compression studies showed that the samples containing a higher volume fraction of pores exhibited higher energy absorption efficiency in the fabricated foam. The maximum energy absorption efficiency ( η ) achieved was ≈93% for the pristine Al alloy foam with ≈50% porosity, which is ≈11% higher than the η value of 9 vol% B4 C samples with similar porosity. Additionally, B4 C particles delay the sudden collapse of cell walls and stabilize the compression behaviour. Adding B4 C improves the η and strength at higher relative density. This fabrication methodology would help us develop foams with a homogenous pore distribution and regular geometry, achieving highly desirable mechanical properties. Abstract : Al–Zn alloy foam reinforced with B4 C particles is fabricated using a space holder technique. The addition of B4 C particles delays cell walls' sudden collapse, leading to improvement in energy absorption efficiency at higher relative densities. This fabrication methodology helps in developing foams with a homogenous pore distribution and regular geometry, achieving highly desirable mechanical properties.